Pengaruh Sumber Daya Manusia dan Bencana Alam Terhadap Pertumbuhan Ekonomi - M. Khairi Luthfi; Khairul Amri (Jurnal Ekonomi Manajemen dan Sekretari, 2023)
This research aims to analyze the influence of human resources and natural disasters on Indonesia's economic growth. Using annual time series data starting from 2008-2022 with multiple linear regression methods and autoregressive distributed lag (ARDL) models. This study reveals that there is no cointegration relationship between economic growth and human development indices and natural disasters. Both in the short and long term, human resources as measured using the human development index have a negative effect in the short and long term. Likewise, natural disasters which are measured using the number of natural disaster evacuees have a negative effect in both the short and long term on Indonesia's economic growth. These findings have implications that solutions to increase economic growth can be realized through economic development policies, ensuring investment in education and human development is right on target and developing disaster emergency response plans and building disaster-resistant infrastructure.